Comparing the General Anti-avoidance Rule of Income Tax Law with the Civil Law Doctrine of Abuse of Law (Part II) - Prebble, Zoë (2015)
This article compares and analyzes how member States of the European Union, the United States of America and the United Kingdom combat tax avoidance through its legal systems. The article addresses issues such as the influence of the Court of Justice of the European Union and the case Cadbury Schweppes in establishing anti-avoidance rules in member States of the European Union and the application of Business Purpose Doctrine in the United States of America and the United Kingdom.